Transformational Islamic Education Ideas Abdurrahman wahid's perspective - Samsudin Samsudin; Widiati Isana; Yasmin Astri (AL-ISHLAH: Jurnal Pendidikan, 2021)
This article examines Abdurrahman Wahid's (often referred to as Gus Dur) views on transformative Islamic education. This is a qualitative study conducted in a library. This research compiled a collection of Gus Dur's writings on transformative Islamic education. The data collection technique used in this study was content analysis. In comparison, the authors used procedures for compiling, connecting, reducing, presenting, and withdrawing data during the data analysis process. According to Abdurrahman Wahid's thinking, this study discovered two concepts of transformative Islamic education: peace education and multicultural education. In informal education, Gus Dur's idea of peace education can be implemented through a sociopolitical lens through cooperative learning strategies. In contrast, in non-formal education, it can be implemented through dialogue and deliberation strategies. Multicultural education is Gus Dur's vision of education to foster heterogeneity in Indonesian society. Because, as Gus Dur points out, Indonesia is made up of numerous ethnic groups, tribes, cultures, and religions. As a result, the Indonesian people face the possibility of conflict over religion, ethnicity, and culture.